Cognitive Mapping of the Key Factors Influencing Blockchain Adoption in Iran's Food Supply Chains - Mohemmi, Zahra; Mostofi, Amirhossein; Jain, Vipul; Samarghandi, Hamed; Dadmand, Fatemeh; Mehrparvar, Maryam (Ram Arti Publishers, 2026)
It is worth mentioning that Blockchain Technology can enhance transparency, trust, and efficiency in a supply chain in general and in food supply chains in particular. Nonetheless, its application in Iran’s food industry is still limited due to technological, organizational, strategic and operational challenges. Unlike previous studies, this paper identifies and structures the key factors influencing blockchain implementation in the food sector supply chain through expert confirmation and Interpretive Structural Modeling (ISM). Twenty-six critical drivers were analyzed to reveal their interdependencies and hierarchical significance. The results of this work highlight that developing efficient and effective food supply chain strategies is the most critical factor for successful blockchain adoption, supported by components such as technological readiness, management commitment, transparency, trust, and system quality. The findings also provided a strategic roadmap, which emphasizes aligning technology adoption with organizational preparedness and policy support. This research contributes to the understanding of blockchain diffusion in emerging economies and offers practical and actionable insights for decision-makers seeking to enhance traceability, efficiency, and stakeholder trust in the complex operations of the food supply chain.
Keywords: 3507 Strategy, management and organisational behaviour; 4010 Engineering practice and education; 4901 Applied mathematics; Food supply chain; Blockchain technology; Interpretive-structural modeling; MICMAC